Laws / tr.by Trevor j.Saunders - Plato ("Middlesex, Eng", 1984)
The reader of The Republic, Plato's best known political work, may well be astonished by the Laws. Instead of an ideal state ruled directly by moral philosophers, this later work depicts a society permeated by the rule of Law.
Keywords: Philosophy